Psycholinguistic: Child Language Acquisition at The Phonological Level - Hutauruk, Bertaria Sohnata; Fazalani, Runi; Ilmi, Darul; Supit, Deisye; Asmaryadi, Ahmad Ilham (Journal for Lesson and Learning Studies, 2023)
The acquisition of children's language at the phonological level in psycholinguistic studies is very interesting to be discussed by experts and researchers. The study of language acquisition in the field of phonology is important in the field of phonology in children. This research was conducted to analyze children's language acquisition. This research is qualitative because it is appropriate to systematically, factually, and accurately describe language acquisition. This type of research is descriptive qualitative. The subjects in this study were children aged 2 to 4 years. The data collection method in this study is observation. Observation or direct observation of the research object is intended to get a clear picture of the existence of the research object and the activities carried out. After the data is collected, a discussion is carried out using the distribution method. The data analysis technique uses descriptive qualitative analysis. The data were analyzed based on the forms and functions in the language of children aged 2-4 years. The study results are that children's language acquisition at the age of 2-4 years is different for each child, but this is considered reasonable because the language acquisition that occurs in each child is not the same. Children aged 2-4 years can use the sound of pronouncing words and sentences in consonant acquisition; children aged 2-4 years can pronounce vowels; while in acquiring syntax, children aged 2-4 years can use the best words and sentences.